Reptiles and amphibians Set 3 (Explorers) - Dalgleish, Sharon; Dalgleish, Sharon Sharon; Shortland Publications (USA) Incorporated (New York Shortland Publications (USA) Incorporated, 1999)
This non-fiction book offers an engaging exploration of reptiles and amphibians, combining vivid illustrations with real photography. It serves as an educational resource for students in Year 3 to 7+, enhancing skills such as distinguishing fact from opinion, interpreting diagrams, and summarizing information. The content spans various subjects, including life sciences and social studies, making it a comprehensive tool for cross-curricular learning.
Includes both illustrations and real photography Designed for Year 3 to 7+ students Focuses on instructional text, understanding fact and opinion, exploring diagrams, scanning texts, summarizing information, and identifying key features of non-fiction texts. Cross-curricular topics include websites for further research, life science, earth and space, social studies, health, physical science, and ICT. A rich resource for visual literacy.
Primary school students
Keywords: Reptiles-Amphibians-Educational resources